Cancer Genetics - Pasche, Boris; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Cancer genetics has revolutionized the practice of medicine as inherited genetic information helps predicts which individuals are at risk of developing various forms of cancer. Furthermore, somatically acquired genetic changes help identify therapeutic targets for patients with several common tumor types such as breast and colon cancer. Cancer Genetics reviews seminal discoveries such as genetic susceptibility to gastric cancer, ethical issues related to cancer genetics, the role of common variants in the development of breast cancer, novel genetic findings related to neuroblastoma, and the role of constitutively decreased TGF-beta signaling, which is emerging as one of the most common causes of colorectal cancer. The book has been written for all clinicians and researchers interested in cancer genetics, including oncologists, genetic counselors and cancer researchers both in academia and in industry. "Genetic alterations are a fundamental component of all cancers. This text highlights critical issues relevant for both basic scientists and clinicians. Recognized thought leaders in the field discuss current knowledge and future challenges." - Steven T. Rosen, M.D., Series Editor
Ethicolegal Aspects of Cancer Genetics -- The Influence of Common Polymorphisms on Breast Cancer -- Hereditary Diffuse Gastric Cancer -- Genetics and Genomics of Neuroblastoma -- TGF-? Signaling Alterations and Colon Cancer.
Keywords: Medicine; Oncology; Human genetics; Medicine & Public Health; Oncology; Cancer Research; Human Genetics